Upper ocean variability and tropical cyclones in the South West Indian Ocean - Mawren, Daneeja (Department of Oceanography, 2019)
Tropical cyclones (TCs) are the most devastating weather phenomenon in nature with the powerful storm surge events occurring when severe and large TCs make landfall along coastlines. Although there have been significant strides in the TC track forecasts over the last 30 years, skills in TC intensity prediction still lag behind. Intensity may be impacted by the mixing length temperature (known as Tdy) and barrier layer thickness (BLT). Similar to cyclones in other tropical ocean basins, tropical cyclones in the South West Indian Ocean also cause significant social and economic damage in southeastern Africa and Madagascar. To forecast TC intensity more accurately, monitoring upper ocean conditions in the South Indian Ocean is of top priority. Two areas in the relatively poorly studied South Indian Ocean where such upper ocean characteristics of relevance to tropical cyclones need to be better understood are the Seychelles Chagos Thermocline Ridge (SCTR) and the Mozambique Channel. In the first part of the study, the variability of Tdy and BLT in the South West Indian Ocean, focused on the SCTR region and their relationships with tropical cyclones are investigated. It is shown that rapid cyclone intensification is influenced by large Tdy values, thick barrier layers and the presence of anticyclonic eddies. Both BLT and Tdy fields are modulated by the westward propagation of Rossby waves, which are often associated with ENSO. For example, the 1997-1998 El Nino shows a strong signal in Tdy, SST and BLT over the South West Indian Ocean. After this event, an increasing trend in Tdy occurred over most of the basin which may be associated with changes in atmospheric circulation. A rise in SST, Power Dissipation Index and frequency of Category-5 tropical cyclones also occurred post-1998. A case study of TC Bansi in the South West Indian Ocean and its relation to upper ocean heat content was presented. This tropical cyclone is of interest due to its unusual track and also because of all the damage it caused. Anomalously deep thermocline and high Tdy values were observed around December 2014-January 2015 in the South West Indian Ocean and analysis of the upper ocean structure during Bansi showed that its rapid intensification to Category 4 was related to its passage over a high Tdy (warm core) eddy region and a deep barrier layer. The second area focussed on, the Mozambique Channel, is not only a region of relatively high TC activity with highly vulnerable coastal populations, but also very energetic in terms of mesoscale ocean eddies and tidal forcing. Changes in upper ocean characteristics in the Mozambique Channel due to tidal forcing are examined as they may have significant impacts on the upper ocean structure and thus influence tropical cyclones which often occur in this region. Two experiments were conducted using the Regional Ocean Modelling System (ROMS); one forced with tides (Tide) and the other experiment without tidal forcing (NoTide). On seasonal time scales, the tidal forcing simulation shows warmer temperatures in the upper layer particularly near strong ocean currents (North East Madagascar Current and South East Madagascar Current). In Tide, warming near these currents is intensified during winter due to the southeast trade winds, while in summer, poleward advection of warmer waters south of 16-17 oS seemed more prominent. On weather time scales, these changes in the upper ocean structure, especially near the coast or in shallow regions can alter the intensity of passing tropical cyclones. When a storm encounters a warm anticyclonic eddy, as the case of TC Japhet studied in the thesis, the SST cooling by the cyclone is substantially reduced, the mixing length temperature is increased and the mixed layer is deepened. These changes can be important for TC evolution. SST variability over the South West Indian Ocean influences southern African summer rainfall and the regional atmospheric circulation either through regional modes as well as influences the landfall frequency of tropical cyclones on Mozambique (Vitart et al., 2003). Besides SST, a link has recently been found between the regional precipitation over southern Africa and tropical cyclone heat potential (a measure of upper ocean heat content) in the South West Indian Ocean (Malan et al., 2013). In this study, the relationships between an index of southern African summer rainfall (SARI) and Tdy in the South Indian Ocean at zero (January-March) and one season (October-December) lag were analyzed. A region in the southern Mozambique Channel, termed as Tdysmc, showed the strongest positive correlation with SARI at zero lag. Another strong but negative correlation with SARI at one season lag is found in the core of the Seychelles Chagos Thermocline Ridge region, termed as Tdycsctr. Composite analysis (neutral with respect to ENSO) indicated that when Tdysmc is enhanced over the South Mozambique Channel during JFM, positive rainfall anomalies prevail over large parts of subtropical southern Africa and the Congo Basin with reduced rainfall occuring over most of Madagascar and northern Mozambique. The rainfall differences are associated with enhanced easterly flow towards Madagascar transporting more moisture towards Mozambique and Tanzania, consistent with the increased rainfall. During positive Tdysmc JFM seasons, more tropical cyclones (TCs) were formed in the SWIO and more of them crossed the Mozambique Channel compared to negative Tdysmc seasons. Furthermore, during positive Tdysmc seasons, the landfalling TC was generated in the Mozambique Channel while during the negative Tdysmc ones, it was formed in the central South Indian Ocean. Positive Tdysmc seasons also have increased number of Category5 TCs in the Mozambique Channel. These results suggest that changes in the mixing length temperature, Tdysmc index which can be estimated from satellite data can be useful to monitor and potentially predict regional precipitation as well as the frequency and intensity of tropical cyclones that impact the south-eastern coast of Africa.